A Smartwatch or Just a Watch? A Validation Study of the Smartwatch KC08 for Measuring Blood Pressure - Susana López-Ortiz; Celia García-Chico; Lisa Musso-Daury; Sara González-Ustio; Saúl Peñín-Grandes; José Pinto-Fraga; Sergio Maroto-Izquierdo; Alejandro Santos-Lozano (Sensors)
(1) Background: The use of wearable cuffless devices has emerged as an out-of-office blood pressure (BP) monitor device to improve the management of hypertension. We aimed to validate a new, low-cost smartwatch for the measurement of BP and, secondarily, to assess its reliability for the measurement of blood oxygen saturation (SpO2) and heart rate. (2) Methods: We compared 1000 pairs of measurements (n = 100) acquired by a smartwatch (KC08) with those measured by a reference device. (3) Results: A total of 100 participants (41 ± 18 years) completed the measurements. The values for the systolic and diastolic BP, heart rate and SpO2 measured with the Smartwatch KC08 and the reference devices differed significantly (p < 0.05). In addition, the Smartwatch KC08 showed a low variability and poor reliability for all the assessed outcomes except for the heart rate. Moreover, no significant heteroscedasticity was observed for the heart rate measured by the Smartwatch KC08 and the reference sphygmomanometer. (4) Conclusions: The main findings of the present study suggest that the Smartwatch KC08 is not yet suitable for daily clinical practice, although it showed low intra-subject variability and reliability for the resting heart rate.